2019
DOI: 10.1016/j.athoracsur.2018.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Two Ventricles Are Not Better Than One in the Fontan Circulation: Equivalent Late Outcomes

Abstract: Dr d'Udekem discloses a financial relationship with MSD and Actelion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…A recent study comparing patients with a 2-ventricle versus a 1-ventricle Fontan demonstrated no difference in survival between the 2 groups, calling into question the wisdom of resorting to a single ventricle strategy among patients with 2 working ventricles. 8 In the face of these sobering SVP results, institutions must consider whether a more optimal outcome can be achieved with SVP or a higher-risk biventricular repair.…”
Section: The Unavoidable Fontan Physiologymentioning
confidence: 99%
“…A recent study comparing patients with a 2-ventricle versus a 1-ventricle Fontan demonstrated no difference in survival between the 2 groups, calling into question the wisdom of resorting to a single ventricle strategy among patients with 2 working ventricles. 8 In the face of these sobering SVP results, institutions must consider whether a more optimal outcome can be achieved with SVP or a higher-risk biventricular repair.…”
Section: The Unavoidable Fontan Physiologymentioning
confidence: 99%
“…2,3 Further, a widely held belief that the outcomes among single ventricle (SV) patients with "2" ventricles (ie, those in whom septation was not done for other anatomic reasons), are superior to outcomes among SV repairs with only "one" ventricle, led to general acceptance of SV strategies in this population. However, the advent of advanced imaging and 3D modeling coupled with recent literature 4,5 challenging the idea that a 2-ventricle Fontan performs better than a 1-ventricle Fontan, encouraged our group to develop novel techniques to achieve a BiV circulation among patients with heterotaxy in whom septation to achieve a twoventricle or one-and-a-half ventricle repair is limited by inability to route the pulmonary venous return toward the left ventricle (LV). This report describes our initial experience in septation/BiV conversion among 5 consecutive patients, utilizing the LV as the subpulmonary ventricle, essentially recapitulating the physiology of congenitally corrected transposition of the great arteries (ccTGA).…”
Section: Perspective Statementmentioning
confidence: 99%
“…In general, the operation has demonstrated its success with a growing population of patients having this unique Fontan circuit physiology. However, with long-term follow up, the circulation of these patients have recently shown to have multisystem effects with both expected and unexpected sequelae (62)(63)(64).…”
Section: Fontan Palliation For Single Ventricle Patientsmentioning
confidence: 99%